Recent advances in low‐cost carbon fiber manufacture from lignin. Issue 2 (26th April 2013) - Baker, Darren A.; Rials, Timothy G.
ABSTRACT The confluence of two US energy policy mandates, the 2012 Corporate Average Fuel Economy Standards and Renewable Fuels Standard #2, provide the opportunity to examine the possibility of high‐value materials from lignin with increased depth. In this case, the desire to provide lighter, low‐cost materials for automobiles to reduce fuel consumption, and to improve the economics of biorefineries for fuel production, have led to an increased interest in low‐cost carbon fiber manufacture from lignin. For this review the authors provide the context of subject matter importance, a cost comparison of potential low‐cost carbon fibers, a brief review of historical work, a review of more recent work, and a limited technical discussion followed by recommendations for future directions. As the available material for review is limited, the author includes many references to publicly available government documents and reviewed proceedings that are generally difficult to locate. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 713‐728, 2013